Módulo de Dados Dinâmicos - MDD: o emprego prático da inteligência territorial - Rodrigo de Freitas Amorim; Thiago França Simonetti (Confins)
Territorial planning and management are complementary and widely discussed topics in Geography and other sciences that seek ways to improve mechanisms for meeting socio-spatial demands. In this sense, based on the scope of this dossier, which aims to discuss methodologies for the development and implementation of a Water Security Panel (PSH), meeting demands on a national and regional scale, this article aims to propose a Dynamic Data Module (MDD), a tool to be used in water resources management. Considering the multi-scale nature of the present proposal, it was necessary to address different units, with a focus on the Semiarid region, where there is greater water insecurity. The data was integrated through the use of API - Application Programming Interface, a set of rules and protocols that allows different systems to interact and communicate with each other in a standardized way. It is necessary to make the most of the entire available infrastructure network, using data sharing between different public bodies to advance decision-making more efficiently, enhancing results and reducing operational costs. In other words, allowing greater speed in responses to demands, management, at the same time as providing the means for discussions and maturation in decisions, at the planning level, which will have greater spatial coverage and permanence.